2021
DOI: 10.11600/rlcsnj.19.2.4873
|View full text |Cite
|
Sign up to set email alerts
|

Tramas en la construcción de la intersectorialidad para atender la primera infancia

Abstract: (analítico)Este artículo presenta los resultados de la investigación cualitativa realizada desde una perspectiva interpretativa-histórica, para comprender la construcción de relaciones intersectoriales en el programa de atención a la primera infancia de Medellín entre el 2004 y el 2014. Se recurrió al análisis documental y a la observación participante en espacios de gestión de políticas públicas y se implementaron entrevistas semiestructuradas a funcionarios gubernamentales y no gubernamentales. La informació… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…How to align the interests of the involved actors, including management, for better socialization to sustain the changes aimed at intersectoral collaboration? Current models considered that successful networks of aligned interests were created by recruiting a sufficient body of allies and translating their interests into the thinking and acting that maintained the network ( Bilodeau et al, 2019 ; Ceballos-Higuita & Otálvaro-Castro, 2021 ; Okeyo et al, 2020 ; Potvin et al, 2005 ). Likewise, Andrade et al (2015) and Holt et al (2018) found that abstract rhetoric could diffuse responsibility without priorities rather than directly addressing the challenges.…”
Section: Discussionmentioning
confidence: 99%
“…How to align the interests of the involved actors, including management, for better socialization to sustain the changes aimed at intersectoral collaboration? Current models considered that successful networks of aligned interests were created by recruiting a sufficient body of allies and translating their interests into the thinking and acting that maintained the network ( Bilodeau et al, 2019 ; Ceballos-Higuita & Otálvaro-Castro, 2021 ; Okeyo et al, 2020 ; Potvin et al, 2005 ). Likewise, Andrade et al (2015) and Holt et al (2018) found that abstract rhetoric could diffuse responsibility without priorities rather than directly addressing the challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Desde esta perspectiva, tales mecanismos y, en general, las asociaciones público-privadas mejorarían la calidad de los servicios y las oportunidades de elección de las personas usuarias, a diferencia de la provisión puramente estatal o la provisión comunitaria (Araujo et al, 2015). Lo cierto, es que la garantía de los derechos en la prestación del servicio de educación inicial se da en un contexto complejo y problemático lo que, en parte, se debe a que en dicho proceso se involucran diversas formas institucionales de las que dependen la materialización del ejercicio de los derechos (Ceballos-Higuita y Otálvaro-Castro, 2021).…”
Section: Introductionunclassified